Indirectly Directors: Duties Owed Below the Board - Barber, Fran (Victoria University of Wellington Law Review, 2014)
In 2012, the High Court of Australia considered the scope of the term "officer" in a case concerning the breach of a statutory duty by a company secretary and general counsel. The equivalent duties under the New Zealand Companies Act 1993 are owed by an ostensibly narrower class. In considering how New Zealand law would apply to the same situation, this article discusses the extent to which directors' duties are, or should be, owed by those below directorship level. It concludes that an expansive interpretation of the "director" definition is unnecessary and undesirable, and that explicitly extending the definition to encompass certain senior managers would create uncertainties for courts and corporate leaders.